Analysis Of Land And Building Tax (Pbb) Contribution To Medan City's Original Regional Income (Pad) - Liza Seftina; Yunita Sari Rioni; An Suci Azzahra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the contribution of Land and Building Tax (PBB) to the Regional Original Income (PAD) of Medan City for the 2020-2024 period. The research method uses a descriptive approach with effectiveness and contribution ratio analysis. Data were obtained from the Regional Tax and Retribution Management Agency and the Regional Finance and Asset Management Agency of Medan City. The results of the study indicate that (1) the realization of PBB revenue in general is not optimal with an average effectiveness of 80.246% and has not reached the target set in 2020-2024, although in 2021 it reached 100.45%; (2) the contribution of PBB to PAD shows a significant value with an average contribution categorized as moderate, but shows fluctuations from IDR 420.17 billion (2020) to IDR 552.72 billion (2021); (3) the decrease in the number of Tax Payable Notification Letters (SPPT) paid is influenced by internal factors (human resource capacity, administrative system) and external factors (taxpayer awareness, economic conditions). The implications of the research indicate the need for improved strategies in optimizing PBB revenue through increasing taxpayer awareness, modernizing the tax administration system, and better coordination between related agencies to support increasing the PAD of Medan City.